Pengaruh Konsentrasi Ampas Tahu dan Susu Skim terhadap Fisikokimia Yogurt Skim Santan - Tengku Mia Rahmiati; Virna Muhardina; Putri Meutia Sari (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2021)
Skim coconut milk is a liquid by-product of coconut oil production with limited utilization in food processing. It has nutritional value such as protein, carbohydrate and mineral, so it is possible to be used as raw material for processing food products, such as yogurt. The use of tofu waste flour and skim milk as prebiotic and protein source is intended to improve the physical quality of yogurt skim coconut milk. This study used a completely randomized design (CRD) with 2 factors and 3 levels (1,5%, 3%, and 4,5%), and several skim milk concentrations (10%, 12,5%, and 15%). The results of this study indicated that the addition of tofu waste flour and skim milk have no significant effect on the viscosity of the coconut milk yogurt. In the organoleptic test, the addition of tofu waste flour showed significant effect on panelist perception of flavor, aroma, and color. The higher the percentage of the flour, the lower the panelist preference on flavor, aroma, and color; flavor. High concentration of flour can increase the total of soluble solid content in yogurt. A concentration of 4.5% tofu waste flour and 15% skim milk produced 13,89 oBrix and 15,44 oBrix soluble solids resulting in the highest viscosity value of 609,6 Cp.